Mirror Versus Substitute: How Institutional Context Affects Individual Motivation for Corporate Social Responsibility - Jasinenko, Anna; Brieger, Steven A.; Haack, Patrick (Journal of Management, 2026)
The institutional perspective on corporate social responsibility (CSR) has discussed two diametrically opposed hypotheses about how institutional context influences CSR. Whereas the mirror hypothesis suggests that CSR is stronger in institutional contexts with stringent CSR-related regulations, the substitute hypothesis posits that CSR is stronger in weakly regulated contexts. Drawing on the micro-CSR literature, we propose that examining individual CSR motivation can help to better understand the effect of institutional context on CSR because it makes focusing on substantively motivated CSR possible, and it can shed light on the hitherto neglected psychological moderators in this relationship. We conducted three studies, obtaining results indicating that institutional trust is an important moderator of the institutional effect on individual CSR motivation. Overall, we found the highest individual CSR motivation when regulatory stringency and institutional trust were high, supporting the mirror hypothesis. However, in contexts of low institutional trust, this positive effect of a strong institutional context was reduced or even reversed. Our study contributes to the literature on the institutional perspective on CSR, micro-CSR, and institutional theory, and it has important practical implications for CSR management.